The ensemble of Keteng-Keteng Telu Ngawan - Adina S Sembiring; Uyuni Widiastuti; Purbatua Manurung; Hendy Obed Sembiring; Ewin Johan Sembiring (Budapest International Research and Critics University, 2021)
The creation of three-segment keteng-keteng (telu ngawan) with high, midle, and low characters, is carried out through the Soprano, Alto, tenor, and Bass frequency approaches, so that the keteng-keteng telu ngawan instrument becomes a “new” musical ensemble called the keteng-keteng Ensemble. Keteng-keteng Telu Ngawan. The frequency of keteng-keteng telungawan with soprano character is on a scale of 261,626-1046.50 Hz, the frequency of keteng-keteng telungawan with alto character is on a scale of 174,614-698,456 Hz, the frequency of keteng-keteng telungawan with tenor character is on a scale of 130,813-523,251, and the frequency of keteng-keteng telungawan bass character is on a scale of 82.4069-329.628. The determination of the tuning of the four keteng-keteng telungawan is done by recording the sound of the four keteng-keteng telungawan then transferring the sound to a string instrument category and entering it into several music tuner applications such as Da Tuner, Guitar Tuna or other similar applications. The results of the music tuner will be entered into the website so that it will automatically know where the frequency of the sound for each keteng-keteng telu ngawan is.